2002
DOI: 10.2144/02333st06_11825a
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Cycle Temperature Optimization of a Closed-Cycle Capillary PCR Machine

Abstract: The performance of a novel thermal cycler has been characterized in a 30-cycle PCR. The device consists of a microcapillary equipped with bidirectional pressure-driven flow and in situ optical position sensors. A 1-µL droplet of reaction mixture moves between three heat zones in a 1-mm i.d., oilfilled capillary using a multi-element scattered light detector and active feedback. The design permits time and number of cycles to be changed without hardware modification, unlike other flow-in-capillary PCR systems. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The main reason for doing it is that the amplification length of each target gene fragment in the present microfluidic system is relatively small, and therefore the time it takes for the solution to flow through the extension zone may be enough to induce the multiplex extension reaction. In addition, it is possible that the primer extension reaction occurs when the reaction solution is inside of the annealing heat zone and between the annealing and extension heat zones (annealing takes places as the reaction solution travels between heat zones) (Chiou et al 2001(Chiou et al , 2002Chen et al 2007b). Unless Fig.…”
Section: Multiplex Pcr Using An Oscillatory-flow Microreactormentioning
confidence: 99%
See 2 more Smart Citations
“…The main reason for doing it is that the amplification length of each target gene fragment in the present microfluidic system is relatively small, and therefore the time it takes for the solution to flow through the extension zone may be enough to induce the multiplex extension reaction. In addition, it is possible that the primer extension reaction occurs when the reaction solution is inside of the annealing heat zone and between the annealing and extension heat zones (annealing takes places as the reaction solution travels between heat zones) (Chiou et al 2001(Chiou et al , 2002Chen et al 2007b). Unless Fig.…”
Section: Multiplex Pcr Using An Oscillatory-flow Microreactormentioning
confidence: 99%
“…Among them, the oscillatoryflow PCR devices have obtained increasing attention in recent years, due to their salient features such as cycle number/dwell time flexibility, ease of real-time detection implementation, large footprint reduction, and ability to process multiple samples in parallel. In 2001, Chiou et al reported a close-cycle capillary PCR thermocycling machine, where the bidirectional pressure-driven flow and in situ optical position sensors have been integrated (Chiou et al 2001(Chiou et al , 2002. Using this device, 30 cycles of a 500-bp product were performed in 23 min with 78% amplification efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Methods relying on passivation agents directly added to the amplification mix generally require optimal relative concentrations of surface modifiers, reagents, and DNA, and potentially fail when used in microchannels of different volumes. To overcome Taq adsorption on the sidewalls of their oscillatory capillary PCR machine, Chiou et al 38,39 reported on the use of high concentrations of Taq DNA polymerase ͑0.18− 0.7 unit/ l͒, flowing into a polytetrafluoroethylene microcapillary over 30 cycles. Here, a static silanization of glass is performed prior to the amplification experiments, allowing us to work with a standard quantity of Taq polymerase ͑0.02 unit/ l͒.…”
Section: B Device Operationmentioning
confidence: 99%
“…Here, a static silanization of glass is performed prior to the amplification experiments, allowing us to work with a standard quantity of Taq polymerase ͑0.02 unit/ l͒. The PCR mixture also contains the biological detergent Tween-20; however, different from previous studies, 38,39 we could not note relevant stability issues for our droplets, which is likely related to the low fluid velocity ͑3 ϫ 10 −3 m / s͒. Glass capillaries treated by the coating solution are tested in the microfluidic devices using the same thermal profile.…”
Section: B Device Operationmentioning
confidence: 99%